Palladacycle Promoted Base Controlled Regio- and Enantioselective Hydrophosphination of 2-Pyridylacrylate/amide and the Cytotoxicity of their Gold Complexes - Jia, Yu-Xiang (2016)
The regioselective asymmetric hydrophosphination of pyridine-functionalized alkenes can be achieved in the presence of stoichiometric amounts of the chiral palladium complex (R)-1. The presence or absence of base affords the respective β- and α-adducts with excellent regiocontrol. Chiral gold-phosphine complexes incorporating the adducts exhibited good in vitro anticancer activity against the breast cancer cell line MDA-MB-231. Selectivity between the cancer cell line and normal cells was also observed.